2023
DOI: 10.1007/s13555-023-01031-w
|View full text |Cite
|
Sign up to set email alerts
|

Public Perceptions, Factors, and Incentives Influencing Patient Willingness to Share Clinical Images for Artificial Intelligence-Based Healthcare Tools

Sophia Ly,
Sophia Reyes-Hadsall,
Lara Drake
et al.

Abstract: Introduction The use of artificial intelligence (AI) as a diagnostic and decision-support tool is increasing in dermatology. The accuracy of image-based AI tools is incumbent on images in training sets, which requires patient consent for sharing. This study aims to understand individuals’ willingness to share their images for AI and variables that influence willingness. Methods In an online survey administered via Amazon Mechanical Turk, sketches of the hand, face, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Sharing images for clinical research, education, and development of image-based AI has associated ethical and legal concerns. Prior studies suggest patients might share their images, especially for clinical purposes, but consent preferences have not been published. Informed consent is not required for using deidentified data for clinical research and education, abiding by US and European laws, and practices protecting privacy remain unstandardized .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sharing images for clinical research, education, and development of image-based AI has associated ethical and legal concerns. Prior studies suggest patients might share their images, especially for clinical purposes, but consent preferences have not been published. Informed consent is not required for using deidentified data for clinical research and education, abiding by US and European laws, and practices protecting privacy remain unstandardized .…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies suggest patients might share their images, especially for clinical purposes, but consent preferences have not been published. Informed consent is not required for using deidentified data for clinical research and education, abiding by US and European laws, and practices protecting privacy remain unstandardized . The CLEAR (Checklist for Evaluation of Image-Based AI Reports in Dermatology) guidelines provide a framework for addressing the challenges of image use for AI in dermatology, but guidelines on consent based on patient preferences are needed …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 51 In addition, the formation of image sets requires the patients’ consent, an aspect investigated by Ly et al, who observed that most patients were not against this, although for body parts such as the face and genitals they were less predisposed than for areas such as the hands. 52 Recent years have also seen the spread of AI-powered chatbots, of which ChatGPT is the most renowned. 53 It is based on deep-learning technology and one of the major risks being observed is the tendency of users to ask questions of a medical nature, including dermatology.…”
Section: The Teledermatology Of the Future: The Use Of Artificial Int...mentioning
confidence: 99%